SISTEM MONITORING KEAMANAN LINGKUNGAN PERUMAHAN MENGGUNAKAN RASPBERRY PI DAN MOTION EYE OS - Inzagia Pratama, Irnaldika; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2023)
Problems that often arise in residential areas are theft or housebreaking. the case above can be solved by using a surveillance camera, but rarely does anyone use it and the drawback of the existing surveillance cameras is that they cannot make direct notifications. In this study, the above problems can be solved by designing a security monitoring tool for the environment around housing based on webcam cameras and Raspberry Pi by utilizing Motioneye OS as a remote monitoring application, recording and capturing images and video results from motion detect and also notifications from pushover app. This study uses the SDLC method, namely the prototype model, in which this method is able to address real needs. The results in testing this study were that MotionEye OS captures and detects movement well and sends the detection results to pushovers in almost all conditions. for an alternative tool to replace the old system, this is quite good where this new system can monitor remotely and use any device and can receive state updates with notifications. With this security monitoring system tool, it is hoped that it can reduce criminal acts in residential areas.